Functional differences of the catalytic and non-catalytic domains in human ADAMTS-4 and ADAMTS-5 in aggrecanolytic activity. - Fushimi, K; Troeberg, L; Nakamura, H; Lim, N; Nagase, H (2008)
ADAMTS-4 (aggrecanase-1) and ADAMTS-5 (aggrecanase-2) are multidomain metalloproteinases belonging to the ADAMTS family. We have previously reported that human ADAMTS-5 has much higher aggrecanolytic activity than human ADAMTS-4. To investigate the different proteolytic activity of the two enzymes, we generated a series of chimeras by exchanging various non-catalytic domains of the two proteinases. We found that the catalytic domain of ADAMTS-5 has higher intrinsic catalytic ability than that of ADAMTS-4. The studies also demonstrated that the non-catalytic domains of ADAMTS-5 are more effective modifiers than those of ADAMTS-4, making both catalytic domains more active against aggrecan, an Escherichia coli-expressed interglobular domain of aggrecan and fibromodulin. Addition of the C-terminal thrombospondin type I motif of ADAMTS-5 to the C terminus of ADAMTS-4 increased the activity of ADAMTS-4 against aggrecan and fibromodulin severalfold. In contrast to previous reports (Kashiwagi, M., Enghild, J. J., Gendron, C., Hughes, C., Caterson, B., Itoh, Y., and Nagase, H. (2004) J. Biol. Chem. 279, 10109-10119 and Gao, G., Plaas, A., Thompson, V. P., Jin, S., Zuo, F., and Sandy, J. D. (2004) J. Biol. Chem. 279, 10042-10051), our detailed investigation of the role of the C-terminal spacer domain of ADAMTS-4 indicated that full-length ADAMTS-4 is approximately 20-times more active against aggrecan than its spacer domain deletion mutant, even at the Glu373-Ala374 site of the interglobular domain. This discrepancy is most likely due to selective inhibition of full-length ADAMTS-4 by heparin, particularly for cleavage at the Glu373-Ala374 bond. However, removal of the spacer domain from ADAMTS-4 greatly enhanced more general proteolytic activity against non-aggrecan substrates, e.g. E. coli-expressed interglobular domain, fibromodulin, and carboxymethylated transferrin.